2018
DOI: 10.1088/1361-665x/aabf0d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical splicing of superelastic Cu–Al–Mn alloy bars with headed ends

Abstract: This paper examines the feasibility of mechanical splicing using a steel coupler to connect headed ends of superelastic Cu–Al–Mn alloy (Camalloy) bars and steel reinforcing bars to be used in concrete structures. Although threading of Camalloy is as easy as that of steel, mechanical splicing using threaded ends requires machining of Camalloy bars into dog-bone shape to avoid brittle fracture at the threaded ends. The machining process requires significant time and cost and wastes substantial amount of the mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The superior ductility without strong hardening observed in Groups G2 to G4 are noteworthy from the viewpoint of seismic applications, where ductility is critical. The small or moderate hardening is important in avoiding brittle fracture at connections (Kise et al 2018). To the authors' knowledge, such superior ductility of single-crystal SMAs-especially in the form of bars of 8-mm diameter and 40-mm gauge length-has not been reported in the literature; however, the orientation dependence of superelasticity (Horikawa et al 1988) and multistage superelasticity (Otsuka et al 1979) were reported for single-crystal superelastic Cu-Al-Ni SMAs.…”
Section: Elasticity and Superelasticitymentioning
confidence: 99%
“…The superior ductility without strong hardening observed in Groups G2 to G4 are noteworthy from the viewpoint of seismic applications, where ductility is critical. The small or moderate hardening is important in avoiding brittle fracture at connections (Kise et al 2018). To the authors' knowledge, such superior ductility of single-crystal SMAs-especially in the form of bars of 8-mm diameter and 40-mm gauge length-has not been reported in the literature; however, the orientation dependence of superelasticity (Horikawa et al 1988) and multistage superelasticity (Otsuka et al 1979) were reported for single-crystal superelastic Cu-Al-Ni SMAs.…”
Section: Elasticity and Superelasticitymentioning
confidence: 99%
“…One may argue that it is better to perform roll-threading at the α þ β phase before the solution-heat treatment because Cu-Al-Mn alloy has excellent cold workability (Kainuma et al 1996). However, this was intentionally avoided here because the rolled threads can deform significantly during the solution-heat treatment, and the high strain at the rolled threads can prevent crystal growth to obtain single crystals (Kise et al 2018).…”
Section: Threadabilitymentioning
confidence: 99%
“…To avoid brittle fracture at the cut threads, however, machining of SMA rods into a dogbone shape is necessary, as demonstrated in superelastic Ni-Ti SMA rods (DesRoches et al 2004;McCormick et al 2007); this process requires significant time and cost and wastes substantial amounts of the material. To address these issues, the feasibility of mechanical splicing was studied between steel rods and Cu-Al-Mn SMA rods with headed ends (Kise et al 2018). In the feasibility study, it was demonstrated that ductile fracture took place apart from the heat-treated headed ends by controlling the microstructure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the application, the SMAs can be used in the forms: (1) fibers and wires used for retrofitting cementitious composites, (2) wires and rebars used for reinforcing concrete structures, and (3) bars used for damping and self-centering devices [19][20][21][22][23][24][25]. Recently, confinement, self-centering devices, energy dissipation devices, and passive control devices have been studied and developed using SMA wires such as works done by Choi et al, Araki et al and Qui et al and Dolce et al [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%